AUDIT INTERNAL ATAS PERSEDIAAN BARANG DAGANGAN PADA PT NUSANTARA INDAH KIA MOBIL SAMARINDA - -, Gadis Paramitha (EKONOMIA, 2014)
Internal audit of merchandise inventory aims to assess the system of internal control for inventory as well know for inventory valuation and presentation of inventory whether it has assessed and presented with reasonable based on generally acceptable accounting principle applicable in Indonesia.As for the proposed hypothesis is alleged that the merchandise inventory in PT Nusantara Indah KIA Mobil Samarinda has not been assessed and presented fairly generally acceptable accounting principles applicable in Indonesia.To carry out the audit of inventory, analysis tools that are used to inventory audit procedures consisting of inspection procedures of compliance test (use the internal control questionnaires and test inventory to sales transactions) and inspection procedures of substantive (observe the inventory check of the company, requesting final inventory list and check whether the presentation of the inventory is in accordance with the generally acceptable accounting principles applicable in Indonesia).From the analysis discussion of internal control is known that in PT Nusantara Indah KIA Mobil Samarinda is effetive for inventory, merchandise inventory held by PT Nusantara Indah KIA Mobil Samarindaactually exist in the barn and no inventory is fictitious, and known method of inventory valuation used by PT Nusantara Indah KIA Mobil Samarinda is average method and applied consistently each period,so that assessment does not deviate from generally acceptable accounting principle applicable in Indonesia.Overall results of the analysis and discussion, it was recognized that a giveb hypothesis is rejected because assessment and presentation of merchandise inventory in PT Nusantara Indah KIA Mobil Samarinda had reasonable based generally acceptable accounting principles applicable in Indonesia.Based on the above facts, suggest to the company in order to maintain accuracy, and maintain consistent accuracy in the assessment and presentation of merchandise inventory.